Laporan kasus : Hemiplegia Dextra dan Afasia pada Stroke Iskemik Embolik - Zahrawanda Ashfarina Muslim; Meutia Maulina (Jurnal Medika Nusantara, 2026)
Ischemic stroke is a leading cause of disability and death worldwide, particularly in the elderly with established cardiovascular risk factors. Atrial fibrillation is a key risk factor, which can trigger ischemic embolic stroke due to the formation of a cardiogenic thrombus. This article reports a case of ischemic stroke in a 74 year old male patient who presented with right limb weakness and speech impairment three days prior to admission. Clinical examination revealed right hemiplegia accompanied by aphasia. A CT scan of the head revealed an ischemic infarction in the left middle cerebral artery. Electrocardiography confirmed atrial fibrillation as the source of the embolism. Furthermore, the patient was found to have severe anemia due to upper gastrointestinal bleeding, which exacerbated his clinical condition. Management was supportive and comprehensive, taking into account his neurological, cardiovascular, and systemic complications. This case report emphasizes the importance of early risk factor detection and a multidisciplinary approach in patients with complex ischemic stroke.